Examining teacher performance from the perspective of principal academic supervision, work environment, and compensation - Pangestu, Fajar Agung; Wijayanti, Wiwik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The teacher is one of the crucial aspects in the administration of education. No matter how good the curriculum, facilities, and school funding are, the teacher is the spearhead of learning. High teacher performance will make it easier for schools to achieve educational goals. So, in-depth research must be conducted to determine what factors influence teacher performance. This research was conducted to measure the relationship between teacher performance and the principal's academic supervision, work environment, and compensation, partially or simultaneously. Meanwhile, the approach used is quantitative. As many as 144 teachers were selected as research samples using a proportional random sampling technique. The research data were collected through a questionnaire instrument distributed and analyzed using multiple linear regression analysis. The results of the study indicate that teacher performance is significantly influenced by the principal's academic supervision (25.80%), work environment (9.62%), and compensation (8.08%). Simultaneously, the three variables contribute 43.5% to the variation in teacher performance. This finding indicates that increasing supervision, creating a supportive work environment, and providing appropriate compensation can improve teacher effectiveness. Theoretically, this study strengthens the empirical basis that external factors play an essential role in shaping teacher performance. Further research is needed to explore the stages of follow-up of academic supervision carried out by school principals in developing teacher performance, such as the most effective mechanisms and models of follow-up of educational supervision.